The (ambivalent) far-right populist stance on the European Union with the example of the Austrian party FPÖ - Guziak, Albert (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
This article explores the attitude towards the European Union represented by right-wing populist parties by the example of the Austrian Freedom Party. Due to the advanced stage of the European integration and a multitude of its positive and negative repercussions, far-right populist parties adopted an antagonistic rhetoric aiming at discrediting and limiting the inﬂuence of the EU in a country, they represent. The FPÖ skillfully shapes a Euro-sceptic discourse in Austria, embracing a populist strategy of manipulation and hostility. The populist itself is, however, far from oﬀering a clear political vision. Based on the reﬂections on populism by Ernesto Laclau, elaborating on the far-right populist strategies of a former FPÖ’s leader Jörg Haider and ﬁnally confronting the party discourse with real political actions, this article constitutes an attempt to show the complexity of a mutual relation between populism and the European Union.
Keywords: Unia Europejska; eurosceptycyzm; skrajna prawica; Partia Wolności Austrii; populizm